Soil factors influencing heavy metal concentrations in medicinal plants - Nayan, Dayang Safinah; Ishak, Che Fauziah (Universiti Putra Malaysia Press, 2013)
This study was conducted with the aim of finding soil factors which influence heavy metals uptake by medicinal plants. The heavy metal concentrations in medicinal plants at 3 different sites (different soil types) and the soils on which the plants grow were analysed. From the correlation analysis, soil properties affect all of the heavy metal concentrations in soils, meanwhile, only Cu and Se concentrations in soils affect their uptake by plants. However, this depends on plant parts (root and foliar), and the soil types. Principal component analysis (PCA) was also conducted to ascertain any patterns in the soil samples in relation to soil chemical characteristics and reinforce the findings from the correlation analysis. From the principal component analysis in this study, total Pb and As concentrations in medicinal plants were correlated with their concentrations in soils; however, they vary according to the soil types.